Digital Monitoring and Information System Regarding the Operational Safety of CO2 Storages - Vladut, Gabriel (Current Overview on Science and Technology Research Vol. 4, 2022)
In order to develop a programmable system for tracking CO2 deposits, the author and a group are a part of an international initiative. The overall goal of the DigiMon project is to significantly speed up the implementation of carbon capture technology by creating and demonstrating a digital monitoring early-warning system that is societally embedded, smart, affordable, and capable of monitoring any subsurface barrier system and CO2 storage reservoir. The aims is to develop and combine distributed fiber-optic sensing technology, seismic point sensors and gravimetric with proven Ethernet-based digital communication and near real-time, web-based smart data processing software with the information of the social partners in the potential risk area. This paper will present the system concept and component blocks. With regard to the environment (offshore or onshore) and new system components offered by market-driven technology development, the system will be made adaptable and interchangeable. Measurement, monitoring, and verification (MMV) is a crucial part of any Carbon Capture System (CCS) project. MMV must show that projects are planned and carried out in a way that is both affordable and acceptable to society. It also ensures safety and security, with a focus on sharing knowledge with the general public and decision-makers. These articles present the system functions and programs for integrated digital monitoring of CO2 storage.